2015
DOI: 10.3892/ol.2015.3832
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-101 suppresses migration and invasion via targeting vascular endothelial growth factor-C in hepatocellular carcinoma cells

Abstract: Abstract. MicroRNAs (miRNAs) are a class of non-coding RNAs 18-25 nucleotides in length,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Anti-VEGF treatment augments the tumor radiation response under normoxic or hypoxic conditions, which is a novel therapeutic strategy in cervical cancer (37). VEGFA and VEGFC, two members of the VEGF family, were recently identified as the predominant tumor metastasis-driving factors in various human cancers types, including renal cell carcinoma (38), hepatocellular carcinoma (39) and cervical cancer (40)(41)(42). The present study identified VEGFA and VEGFC as targets of miR-144 via directly binding to the 3'-UTRs of VEGFA and VEGFC mRNA in a dual luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-VEGF treatment augments the tumor radiation response under normoxic or hypoxic conditions, which is a novel therapeutic strategy in cervical cancer (37). VEGFA and VEGFC, two members of the VEGF family, were recently identified as the predominant tumor metastasis-driving factors in various human cancers types, including renal cell carcinoma (38), hepatocellular carcinoma (39) and cervical cancer (40)(41)(42). The present study identified VEGFA and VEGFC as targets of miR-144 via directly binding to the 3'-UTRs of VEGFA and VEGFC mRNA in a dual luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-C is an important and a major mediator of physiologic and pathogenic angiogenesis of HCC [29] . The knockdown of VEGF-C markedly inhibited invasion and migration of liver cancer cells [30] . Accordingly, EXT and isoepoxypteryxin treatment significantly reduced hepatic VEGF-C levels in TAA-induced HCC rat model.…”
Section: Table 1: Effect Of Different Group Treatment On Histopatholomentioning
confidence: 93%
“…Overexpression of miRNA-96 is observed in HBV-related HCC. In HCC cell lines, miRNA-101 targets VEGF-C resulting in the suppression of invasion [147]. miRNA-21 has been found upregulated in HCC and its degradation can be used as target in therapeutics [148].…”
Section: Noncoding Rnasmentioning
confidence: 99%